Analysis nonlinear vibrations of the three - phase composite shallow cylindrical shell - TTH, Huyen; QT, Luot (International Journal of Advanced Engineering Research and Science, 2022)
This paper presents the results the study nonlinear vibrations of the three-phase composite shallow cylindrical shell. The differential equation describing the nonlinear vibrations of the shell is solved by the Newmark direct integration method combined with the Newton Raphson iterative method. Numerical simulation by finite element method is used to calculate the vibration of the structure. The results of the digital survey allow to make quantitative comments, technical recommendations, help the designers and users to orient effective applications in technical fields.